The concept of LISA and its current status - Ramlan, Mohd Fauzi (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The sustainabilty of food production has always been the big question when environmental, economic and social related factors are involved. Eventhough profit making is still the main agenda, issues related to degradation of soils, polluted underground water, high chemical content in the food products and high labor and prodcution cost remains to be the important subjects. In Malaysia, a conventional agriculture involved large capital and are largely planted as single crop or monocropping. It also involved an intensive labor and has ben associated with excessive use of pesticide. This paper stressed on the Low Input Sustanable Agriculture (LISA). LISA stressed on three important aspects namely on the economic sustanability; environment sustainability, and social sustanability. Sustanability developement goals 11, 13, 15 stressed the sustainable in cities and cominities; climate action, and life on land, respectively. As such these goals are bases of LISA in preserving ecological factors, increasing the efficiency of non-renewable sources while sustaininlng the economic viability. The use of modern and environemental freindly fertiliser has shown the positive results in many part of China. Thus, LISA is the agricuture system based is on the principles of meetig the needs without compromising the future generations of food production.